Sacred Networks Vis A Vis Sovereign Interests: Faith-Based Diplomacy and the Western Sahara Question in Indonesia-Morocco Relations - Wafa , Mohamad Laudza’i; Triwahyuni , Dewi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The paper explores the foundations and limitations of faith-based diplomacy in Indonesia-Morocco relations, particularly through the Western Sahara dispute. Drawing on a qualitative case study, it analyses interviews, official documents, and secondary sources to assess how religious cooperation has shaped bilateral engagement. The analysis indicates that faith-based diplomacy contributed to strengthening symbolic affinity, trust, and transnational working religious networks between both countries. Still, these ties have not changed Indonesia’s cautious and neutral position over Morocco’s territorial claim. It is concluded that although religion may help facilitate people-to-people relations and normative legitimacy, ultimately sovereign interests and domestic political considerations trump all in sensitive geopolitical matters. This article highlights that faith-based diplomacy has symbolic and social power in the religious, development and humanitarian discourses of contemporary international relations but limited potential to shape state behaviour over territorial disputes; it contributes to scholarship on religion in international relations.